Safety and efficacy of a feed additive consisting of l‐tryptophan produced with Corynebacterium glutamicum KCCM 80346 for all animal species (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the feed additive consisting of l‐tryptophan produced by fermentation with a genetically modified strain of Corynebacterium glutamicum (KCCM 80346) when used as a nutritional additive in feed and water for drinking for all animal species and categories. Viable cells of the production strain and its DNA were not detected in the additive. l‐Tryptophan manufactured by fermentation using C. glutamicum KCCM 80346 does not give rise to any safety concern with regard to the genetic modification of the production strain. The use of l‐tryptophan (≥ 98%) produced with C. glutamicum KCCM 80346 to supplement feed is safe for non‐ruminant species. There may be a risk for an increased production of toxic metabolites when unprotected tryptophan is used in ruminants. The FEEDAP Panel has concerns on the use of l‐tryptophan in water for drinking. The use of l‐tryptophan produced with C. glutamicum KCCM 80346 in animal nutrition raises no safety concerns to consumers of products from animals receiving the additive and to the environment. l‐tryptophan produced with C. glutamicum KCCM 80346 is not irritant to the eyes and skin, and it is not a skin sensitiser. The additive l‐tryptophan is regarded as an effective source of the amino acid l‐tryptophan for all non‐ruminant species. To be as efficacious in ruminants as in non‐ruminants, it should be protected from ruminal degradation.